ANALISIS KOMPARASI USAHATANI KELAPA SAWIT SWADAYA MENURUT TIPOLOGI LAHAN DI KABUPATEN INDRAGIRI HILIR - Riyadi Mustofa; Novia Dewi; Jum’atri Yusri (Indonesian Journal of Agricultural Economics, 2016)
Farmers income palm patterns of independent smallholders in Indragiri Hilir Distric were low, presumably because differences of land typology. There are four typologies of land in Indragiri Hilir, namely mainland land, peat tidal, peat marine and marine. This study aims to determine the farmers palm income based typology of land. The quantitative analysis is done by building a model of multiple linear regression analysis with dummy variables. This research show that farmers income palm patterns of independent smallholders in the Indragiri Hilir District on the mainland land typology is the best compared to the typology of peat tidal, peat marine and marine. The highest net income is on the mainland soil typology, typology further peatland tidal and coastal lands.